Indirect Savings from Public Procurement Centralization - Clarissa Lotti; Arieda Muço; Giancarlo Spagnolo; Tommaso Valletti (Center for Economic Studies and ifo Institute (CESifo), 2023)
Centralization of public procurement can lower prices for the government's direct purchase of goods and services. This paper focuses on indirect savings. Public administrations that do not procure directly through a central procurement agency might benefit from the availability of centrally-procured goods. We exploit the introduction of a central purchasing agency in Italy and find that prices came down by 22% among administrations that bought autonomously. These indirect effects appear to be driven by informational externalities, especially for less competent public buyers purchasing technologically more complex goods. Accounting for indirect savings increases the estimate of direct ones.
Keywords: D44; H11; H57; H83; L38; L88; 330; centralization; informational externalities; procurement; public contracts